Sistem Informasi Pelayanan Publik Berbasis Web Pada Badan Kesatuan Bangsa dan Politik Provinsi Lampung - Zunnur Aini; Dona Yuliawati (Jurnal SIMADA (Sistem Informasi dan Manajemen Basis Data), 2022)
Political and National Unity Lampung Affair is an organization that has the task to support the Governor in carrying out the national and political unity in the province. One of the functions is to carry out policies, coordinate, and monitor, and evaluate the foreigners, community organizations, and research in Lampung Province. Political and National Unity Lampung Affair serves the community in the management of permits or research/research recommendations, certificates of foreigners' reports, and certificates of the existence of mass organizations. The government as a public servant is demanded to perform well so that it can produce services truly excellent and based on the community needs. The system development method used waterfall. Tools used for system development include context diagrams and Data Flow Diagram (DFD). The Web-Based Public Service Information System of the Lampung Province National Unity and Politics Agency was an innovation and a transparent and quality information service delivery media that complied with constitutional regulations.Keywords : Information System of Public Service, Web, Waterfall,  Information System